Der sozialgeographische Einfluss des Kastenwesens auf Siedlung und Agrarstruktur im südlichen Indien.: Teil I: Kastenwesen und Siedlung. Einwirkungen des Kastensystems auf die sozialgeographische Struktur und das Funktionsgefüge ländlicher Siedlungen im südlichen Indien (Andhra Pradesh) - Bronger, Dirk (ERDKUNDE, 1970)
The most significant key to an understanding of the social and economic geographical factors which form India’s cultural landscape lies in a knowledge of the castesystem. This study discusses the influences of the caste system on the socio-economic structure and the network of functions in a particular part of the cultural landscape, i. e. in a rural settlement. The rigidity of the system, which ties the members of a given caste, especially a lower one, to a traditional occupation, is still extant, even in our days, and can be observed in non-industrial, rural areas. In addition to such institutional restrictions on a free choice of occupation, a change of occupation or working place is made even more difficult by personal-legal and socio-psychological impediments. These impediments can hardly be overcome by the individual, because in non-industrial rural areas no additional lines of trade are offered by the village or within easy reach of the village. It is indeed the lack of alternatives which tends to render the caste-system in this part of South-India even more rigid. The organization of castes in an Indian village and the socio-economic conditions of the individual are most impressively reflected by the lay-out of the settlement. The individual will try to have his house in the close neighbourhood of his caste-fellows, with the effect that each caste has a separated quarter of its own within the village. I t often depends on the size of the settlement to what extent the division of quarters can be noticed. Since the castes mostly carry out their traditional functions, the division of caste-quarters is at the same time a functional lay-out of the village. While the hierarchical order of castes is mainly responsible for the existence of separate quarters, the economic contrast among members of the same caste can be noticed in a more differentiated lay-out of the respective buildings, since these contrasts account for different buildings within the same quarter. As the Settlement grows these differences of lay-out become more complicated. To the present day these caste-quarters, clearly representing the system’s inertia in the lay-out, have proved almost unchangeable. The old divisions are only recently beginning to be overcome, which is due to overpopulation and high density-rates and also to the fact that the individual becomes more and more conscious of his own personality.